STUDENTS’ PERCEPTION TOWARDS THE USE OF GOOGLE CLASSROOM IN WRITING SUBJECT - Eva Fitriani Syarifah (Journal of English Language Learning, 2021)
Google Classroom is one of features from Google that mostly used by the educators recently. It helps them to submit and organize the students’ assignments. The main purpose of this study is to investigate students’ perception towards the use of Google Classroom in writing subject. The study is carried out through a qualitative research design. The study involved the students of higher education who have used Google Classroom in writing subject for at least one semester. The data obtained through questionnaire and interview. The data obtained were analyzed by using thematic analysis. Finding revealed that students perceive it as a tool that helps them to submit the assignment easily. They assumed that it assist them in managing the assignment better. Thus, it can be concluded that Google Classroom is useful for both lecturer and student in writing subject. Keywords: Google Classroom, writing, technology integration, technology in ELT